A bioluminescent sensor for highly selective and sensitive detection of human carboxylesterase 1 in complex biological samples. Issue 15 (26th January 2016) - Wang, Dan-Dan; Jin, Qiang; Zou, Li-Wei; Hou, Jie; Lv, Xia; Lei, Wei; Cheng, Hai-Ling; Ge, Guang-Bo; Yang, Ling
Abstract : A highly selective and sensitive bioluminescent sensor (DME ) for real-time monitoring of human carboxylesterase 1 (hCE1) activities in complex biological samples and bio-imaging of endogenous hCE1 in living cells. Abstract : A highly selective and sensitive bioluminescent sensor (DME) for human carboxylesterase 1 (hCE1) has been developed and well characterized. DME could be used for real-time monitoring of hCE1 activities in complex biological samples and for bio-imaging of endogenous hCE1 in living cells.